2010
DOI: 10.1111/j.1398-9995.2010.02476.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor necrosis factor-alpha treatment reduces allergic responses in an allergic rhinitis mouse model

Abstract: This study shows that the TNF-α inhibitor infliximab induces anti-allergic effects by decreasing local and systemic Th2 cytokine (IL-4) production, total and OVA-specific IgE levels, adhesion molecule (E-selectin) expression, and eosinophil infiltration into the nasal mucosa in an allergic rhinitis model. Therefore, infliximab should be considered as a potential agent in treating allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 18 publications
3
52
0
2
Order By: Relevance
“…In our study, TNF-a levels of the serum and nasal samples in AR patients were significantly higher than in the control group. A possible explanation of high TNF-a could be that it is a principal mediator of the acute inflammatory response, including allergic rhinitis [24,25], and could be related to the lower levels of IL-10. A reduction of IL-10 with the increase of TNF-a could be attributed to the worsening of the allergy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, TNF-a levels of the serum and nasal samples in AR patients were significantly higher than in the control group. A possible explanation of high TNF-a could be that it is a principal mediator of the acute inflammatory response, including allergic rhinitis [24,25], and could be related to the lower levels of IL-10. A reduction of IL-10 with the increase of TNF-a could be attributed to the worsening of the allergy.…”
Section: Discussionmentioning
confidence: 99%
“…The influx of these inflammatory cells into nasal mucosa, in turn, results in production of leukotrienes and histamine, as well as proinflammatory cytokines, which is characterized by nasal hyposmia, hyperreactivity and blockage [25]. TNFα, an important proinflammatory cytokines produced by mast cells and eosinophils, is critical for the pathogenesis of AR [5, 26]. In previous studies, the level of TNFα has been found to be effectively inhibited by intranasal administration with steroids [27].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response is associated with increased number of eosinophils, and upregulated levels of proinflammatory cytokines, such as TNF-α, IL-4, IL-5 and IFN-γ [5-7]. The interaction between these cytokines and glandular structures results in a variety of symptoms, including rhinorrhea, nasal obstruction, post nasal drainage, sneezing, and nasal irritation [8].…”
Section: Introductionmentioning
confidence: 99%
“…After consulting the relevant literature, we found the amount of OVA used in animal models generally ranges from 10 to 100 μg (Yamaki et al, 2005;Tumes et al, 2007;Liu et al, 2010;Oh et al, 2011), whereas the amount of Al(OH) 3 ranges from 1 and 5 mg. Moreover, there are several forms of Al(OH) 3 used in these experiments including powder, gel, solution, and other dosage forms (Yamaki et al, 2005;Zhao et al, 2005;Su et al, 2006;Tumes et al, 2007;Mo et al, 2011). Our study focused on these three dosage forms (powder, gel, and solution) in the production of an AR animal model.…”
Section: Discussionmentioning
confidence: 99%